Adventure Legal Learning: Membangun Kesadaran Hukum dan Kepemimpinan Remaja melalui Eduka-Game di Alam Terbuka - Rahmawati, Debrina; Fitriana, Nurin (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to enhance legal awareness and leadership skills among high school students in Dau District, Malang Regency through the Adventure Legal Learning program. The background of this activity is the low level of legal understanding, leadership ability, and the limited use of interactive learning methods in the school environment. This community service project applies a participatory approach, actively involving students as key participants. The methods used combine legal education, educational games based on Eduka-Game, and outdoor outbound activities designed to foster values of responsibility, discipline, and leadership. The implementation includes legal counseling, group discussions, case simulations, collaborative games, and reflection sessions, with evaluation conducted through behavioral observation and participant response questionnaires. The results indicate a significant improvement in students’ legal understanding, communication skills, teamwork, empathy, and discipline. Moreover, positive leadership behaviors and stronger legal awareness emerged among participants. This experiential learning approach proved effective in developing responsible, empathetic, and integrity-driven young individuals capable of becoming agents of change in their communities. However, variations in individual leadership and empathy skills remain challenges that need further attention and development in future programs.